Energy Modernisation and Regional Reorganisation of the Southern Andes: The Unexpected Materialities of the Southern Peruvian Gas Pipeline - Nina Montes de Oca; Sébastien Velut (Revue de Géographie Alpine)
Since 2004, gas operations in Camisea have been restructuring the Peruvian energy system. The pivot of Peruvian energy production has shifted from the high mountains and their water resources to the Andean foothills, and a vast political programme of gas network construction and gas massification was launched in the mid-2000s. This article aims to question the materiality of the energy change implemented in the Southern Andean region of the country, which does not involve renewable energy, but has crystallised around a gas pipeline project and its outcomes (thermal power plants, urban networks, etc.). From an interpretive framework articulating notions of development imaginaries with a critical approach of the materiality of energy modernisation, this article builds its analysis drawing from a variety of sources that combine field work and the vast number of documents published on the project in order to map energy change in this region, and the values associated to it. While the symbolic object of the Southern Peruvian Gas Pipeline is presented in discourses as the triumphant advent of energy modernisation in which the State is the central actor, it has given rise to fragmented energy materialities, and a distorted energy change, moving away from its primary social goal.